Financial crisis impact on the Lithuanian stock market - Bareikienė, Daiva; Sūdžius, Vytautas (Business: Theory and Practice, 2011)
The purpose of this article is to evaluate financial crisis impact on the Lithuanian stock market. Nowadays financial crisis of 2007–2010 is a very popular issue between society, government and financial institutions. Such an event changed everyone’s daily routine. Besides, this important and specific crisis affected goals, strategies and plans of many institutions. After this crunch lots of investors started to doubt about the reliability of stock market. For this reason, the factors which make impact on the Lithuanian stock market, are determined and the characteristics of the period of 2003–2010 in the Lithuanian stock market are presented. The method of the moving averages is used in order to analyze the dynamics of the stock market and to forecast the perspectives of the market. The results of the research showed that the financial crisis made the biggest negative impact on the Lithuanian stock market during the year 2008. Despite this, the market is slowly recovering and it is possible that it will start to develop in the near future.Article in Lithuanian.Finansų krizės poveikis Lietuvos vertybinių popierių rinkaiSantrauka. Nagrinėjama Lietuvos vertybinių popierių rinkos būklės kitimo dėl susidariusios finansų krizės problema. Nustatomi Lietuvos vertybinių popierių rinkos ypatumai, veiksniai, darantys didelį poveikį OMXV indekso Santraukakitimui. Pateikiamos Lietuvos vertybinių  popierių  rinkos  2003–2010  m.  charakteristikos,  pritaikomas  slankiųjų  vidurkių  metodas.  Analizuojamas  finansų krizės poveikis investuotojų nuomonei apie investavimą ir artimiausi investuotojų lūkesčiai. Remiantis atlikta apklausa ir OMXV indekso  kitimo  dinamika  nustatomos  investavimo  perspektyvos.  Tyrimas  atskleidė,  kad  didžiausias  neigiamas  finansų  krizės poveikis Lietuvos vertybinių popierių rinkai pasireiškė 2008 m., tačiau rinka iš lėto atsigauna ir tikėtina, kad artimoje ateityje Lietuvos vertybinių popierių rinka pradės sparčiai plėstis.Reikšminiai  žodžiai: finansų  krizė,  vertybinių  popierių  rinka,  slankiųjų  vidurkių  metodas,  investavimas,  OMXV  indeksas, amplitudė.